Human Macrophages Polarized by Interaction with Apoptotic Cells Produce Fibrosis-Associated Mediators and Enhance Pro-Fibrotic Activity of Dermal Fibroblasts In Vitro - Aleksandra Maksimova; Ekaterina Shevela; Lyudmila Sakhno; Marina Tikhonova; Aleksandr Ostanin; Elena Chernykh (Cells, 2023)
Apoptosis and subsequent removal of dead cells are an essential part of wound healing. Macrophages phagocytize apoptotic cells (efferocytosis) and contribute to the resolution of inflammation. However, their participation in fibrogenesis and the mechanisms of influence on this process remain unclear. In the present study, we focused on the fibrogenic properties of human monocyte-derived macrophages polarized in the M2 direction by interaction with apoptotic cells. We studied their influence on the proliferation ([3H]-thymidine incorporation), differentiation (by the expression of α-SMA, a myofibroblast marker) and collagen-producing activity (ELISA) of dermal fibroblasts compared to classically (LPS) and alternatively (IL-4) activated macrophages. Macrophages polarized by the interaction with apoptotic cells had a unique phenotype and profile of produced factors and differed from the compared macrophage subtypes. Their conditioned media promoted the proliferation of dermal fibroblasts and the expression of α-SMA in them at the level of macrophages stimulated by IL-4, while the stimulating effect on the collagen-producing activity was more pronounced compared to that of the other macrophage subtypes. Moreover, they are characterized by the high level of production of pro-fibrotic factors such as TIMP-1, TGF-β1 and angiogenin. Taken together, M2-like macrophages polarized by efferocytosis demonstrate in vitro pro-fibrotic activity by promoting the functional activity of dermal fibroblasts and producing pro-fibrotic and pro-angiogenic factors.